2011
DOI: 10.1017/s0033291711002169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in problem-solving appraisal after cognitive therapy for the prevention of suicide

Abstract: Cognitive therapy for the prevention of suicide provides rapid changes within 6 months on negative problem orientation and impulsivity/carelessness problem-solving style. Given that individuals are at the greatest risk for suicide within 6 months of their last suicide attempt, the current study demonstrates that a brief cognitive intervention produces a rapid rate of improvement in two important domains of problem-solving appraisal during this sensitive period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Consistent with our hypotheses, we found that SCB RFL, belief in the importance of dealing with and finding solutions for adversity, uniquely contributed to the total RFL mediated effects, and thus at least partially accounted for relations between risk factors and both suicide ideation and attempt. Research shows that low reliance on strategies that address the direct management of the problem is associated with suicidal ideation (Elliott & Frude, ; Schotte & Clum, ) and suicidal behavior (Lauer, de Man, Marquez, & Ades, ), and a body of research shows that interventions designed to increase problem‐solving and coping skills demonstrated a reduction in suicidal ideation (Pollock & Williams, ) and suicidal behavior (Joiner, Voelz, & Rudd, ; Ghahramanlou‐Holloway, Bhar, Brown, Olsen, & Beck, ) although this is not invariably so (Fremouw, Callahan, & Kashden, ; Kashden, Fremouw, Callahan, & Franzen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our hypotheses, we found that SCB RFL, belief in the importance of dealing with and finding solutions for adversity, uniquely contributed to the total RFL mediated effects, and thus at least partially accounted for relations between risk factors and both suicide ideation and attempt. Research shows that low reliance on strategies that address the direct management of the problem is associated with suicidal ideation (Elliott & Frude, ; Schotte & Clum, ) and suicidal behavior (Lauer, de Man, Marquez, & Ades, ), and a body of research shows that interventions designed to increase problem‐solving and coping skills demonstrated a reduction in suicidal ideation (Pollock & Williams, ) and suicidal behavior (Joiner, Voelz, & Rudd, ; Ghahramanlou‐Holloway, Bhar, Brown, Olsen, & Beck, ) although this is not invariably so (Fremouw, Callahan, & Kashden, ; Kashden, Fremouw, Callahan, & Franzen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, researchers have reported that SPSI-R scores have utility for discriminating between suicide attempters and both non-suicidal psychiatric patients and non-suicidal controls (Fitzpatrick, Witte, & Schmidt, 2005; Sadowski & Kelley, 1993). The SPSI-R and SPSI-A both differentiated recent suicide attempters from a normative sample (Ghahramanlou-Holloway, Bhar, Brown, Olsen, & Beck, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…A second treatment option, Cognitive Therapy (CT), views suicide attempts as dysfunctional coping strategies for dealing with feelings of severe distress (Ghahramanlou-Holloway, Brown, & Beck, 2008). A primary aim of CT, therefore, is to enhance problem-solving skills, ensuring that suicide is not the only option for distressed individuals (Ghahramanlou-Holloway, Bhar, Brown, Olsen, & Beck, 2012). CT has been shown to be efficacious in treating those who have made prior suicide attempts, with a 50% reduction in the recurrence of re-attempt (Brown et al, 2005).…”
Section: Risk and Protective Factors For Suicide And Their Relevance mentioning
confidence: 99%